Criminal liability for child deaths in custody and the Corporate Manslaughter and Corporate Homicide Act 2007 - Arthur, Raymond (2018)
It is a scandal that in the 21st century child offenders, some of society’s most vulnerable and disadvantaged individuals, still die in the care of the State. Deteriorating and potentially lethal conditions in youth custodial institutions throw into sharp relief the ineffectiveness of the Corporate Manslaughter and Corporate Homicide Act 2007 to operate as a deterrent against unsafe custody practices. Despite applying to adult and child deaths in custody, the Act has never been invoked to prosecute such a fatality. The applicability of corporate manslaughter to child deaths in custody has been almost completely neglected by legal scholars. This article addresses such dereliction of academic scrutiny by analysing how the corporate manslaughter offence might interact with the labyrinthine youth custody system. The conclusion is that the complexity of the system, combined with the technicalities of the Act, would lead to obfuscation at every step of the prosecution process. The death in custody provisions in the Act need to be amended if they are to provide any meaningful protection for vulnerable children in custody. At present the UK is not complying with its duty under Article 2 of the European Convention for the Protection of Human Rights and Fundamental Freedoms 1950 to secure the right to life by putting in place effective criminal law provisions to deter the commission of offences against the person in custodial institutions. There must be systemic change in the attitudes, policies and accepted practices which generate the routine and systematic degradation of the rights of children in custody in the UK